Visualização gráfica dos fundamentos da lógica matemática por meio de diagramas de conjuntos - Peach, Glen (2017)
The purpose of this work is to propose a method that allow to bring the fundamentals of mathematical logic to high school through the use of set theory, however making the whole approach of the subject through diagrams, making it possible to avoid, for the demonstrations and understanding necessary to the development of the subject, the rigors of writing used in mathematical logic, which, in a first contact, tend to discourage the interest of beginning students.